Dose-response effects of gamma irradiation on colour and antioxidant activity of wild Malva neglecta - Pinela, José (2015)
Radiation processing technology has been used to improve food security, safety and quality. However there are a few reports in the literature on the effect of irradiation on bioactivity of herbs and medicinal plants [1]. Hence, the present work was undertaken to investigate the dose-response effects of gamma irradiation on the colour and antioxidant activity of wild Malva neglecta Wallr. In the north-eastern of Portugal, this annual herbaceous plant is traditionally eaten raw as leafy vegetable or prepared in herbal beverages due to its disinfectant and anti-inflammatory properties [2]. Dried M. neglecta samples were exposed to 0 (control), 1, 5 and 10 kGy of γ-rays in a 60Co experimental chamber. After irradiation, the values of CIE L* (lightness), a* (redness) and b* (yellowness) were measured using a Minolta colorimeter; and the antioxidant activity determined in decoction preparations through the DPPH (2,2-diphenyl-1-picrylhydrazyl) free radicals scavenging activity assay, reducing power by the ferricyanide/prussian blue assay, and lipid peroxidation inhibition by β-carotene/linoleate and thiobarbituric acid reactive substances (TBARS) assays. The results suggest that the irradiation treatment with doses up to 10 kGy have no influence on trichromatic colour values L*, a* or b*. However, the effect on the antioxidant activity was somehow different. Samples irradiated with doses of 1 and 5 kGy exhibited higher antioxidant performances than the non-irradiated control in the ferricyanide/prussian blue and TBARS assays. Otherwise, irradiation dose of 10 kGy led to a decrease in antioxidant activity (showing higher EC50 values) in all in vitro assays. Overall, this study demonstrated that gamma irradiation at 10 kGy can adversely affect the antioxidant activity of M. neglecta decoctions, but has no effect on colour parameters.